2000
DOI: 10.1364/ao.39.005854
|View full text |Cite
|
Sign up to set email alerts
|

Roughness and light scattering of ion-beam-sputtered fluoride coatings for 193 nm

Abstract: Scattering characteristics of multilayer fluoride coatings for 193 nm deposited by ion beam sputtering and the related interfacial roughnesses are investigated. Quarter-and half-wave stacks of MgF 2 and LaF 3 with increasing thickness are deposited onto CaF 2 and fused silica and are systematically characterized. Roughness measurements carried out by atomic force microscopy reveal the evolution of the power spectral densities of the interfaces with coating thickness. Backward-scattering measurements are presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…In contrast, PSD data obtained from electropolished materials typically do not exhibit straight lines on a log/log plot but display two regions of strong curvature, as will be seen later. More generally, the PSD of a niobium surface prepared by various methods can be fruitfully decomposed into contributions from each of these types of models [22,26,[35][36][37]:…”
Section: B Shifted-gaussian Model [34]mentioning
confidence: 99%
“…In contrast, PSD data obtained from electropolished materials typically do not exhibit straight lines on a log/log plot but display two regions of strong curvature, as will be seen later. More generally, the PSD of a niobium surface prepared by various methods can be fruitfully decomposed into contributions from each of these types of models [22,26,[35][36][37]:…”
Section: B Shifted-gaussian Model [34]mentioning
confidence: 99%
“…The first two parameters (K, scaling factor; n, slope 1) correspond to the fractal model (adequate for most substrates). They are similar for the three samples, although the substrate and coating material of sample C differ from 23 It seems that gold tends to form slightly smoother coatings than titanium nitride and k corr is a measure of the grain size. Both coatings have a grain size of ¾40-50 nm.…”
Section: Obtaining Objective Information From Combined Psdmentioning
confidence: 86%
“…A more detailed description of our approach of the combined-model PSD can be found in Ref. 23. Figure 5 shows an example of this fitting procedure.…”
Section: Obtaining Objective Information From Combined Psdmentioning
confidence: 99%
“…However, it has been observed that several coatings show the formation of superstructures uniformly distributed along the surface. 23,24 This induces a local maximum in the lower frequencies of the PSD that cannot be described satisfactorily by any of the previous models. An example is represented by the PSD of Fig.…”
Section: A Overview Of Models Applied In Surface Characterizationmentioning
confidence: 92%
“…The results of this study have been published elsewhere. 23,24 Table 2 summarizes the produced designs, where the thickness units are optical quarter-waves and the design wavelength is 193 nm. MgF 2 and LaF 3 were used as the low-and high-index materials, respectively.…”
Section: A Atomic Force Microscope Measurements and Calculation Of Ementioning
confidence: 99%